Pemanfaatan Limbah Botol Plastik sebagai Produk Ramah Lingkungan dan Bernilai Ekonomi melalui Inovasi Tempat Pensil “ReBloom” - Yuyun Setyawati; Ezar Nafis Bramantara; Muhammad Romadhoni Adi Setiawan; Muhammad Yasin (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
The problem of plastic waste in Indonesia is increasingly urgent as plastic consumption increases and sustainable management is lacking. This research aims to explore the potential of utilising plastic bottle waste as a creative and environmentally friendly product in the form of "ReBloom" pencil case. This research uses a descriptive quantitative approach, which collects data from respondents aged 18-25 years old in Surabaya to measure perceptions and interest in recycled products. The study results show that the majority of respondents are interested in environmentally friendly products at an affordable price. The business feasibility analysis revealed that ReBloom has a positive economic outlook with a break-even point that can be achieved within a certain production quantity. Besides contributing to the reduction of plastic waste, the product also raises public awareness of the importance of recycling and circular economy. Digital marketing strategies and collaboration with communities are proposed to increase market acceptance. This research confirms that sustainability-based innovation can be a promising business opportunity while contributing to environmental preservation.